PENGARUH TEMPERATUR TERHADAP EFISIENSI STERILIZER DAN KUALITAS MINYAK YANG DIHASILKAN - RM randa, Sulaiman, (Menara Ilmu, 2018)
Sterilizer is a pressurized vessel used to boil oil palm. Sterilizer uses steam as a heating mediumderived from a steam turbine with a temperature of 1000C-1400C. boiling on sterilizer will affectthe yield of palm oil. the higher the sterilizer temperature, the faster the boiling will be and themore oil produced. this is because the viscosity of oil in the palm fruit down when pressed andeasily separated from the fruit. the water contained in the oil will convert the oil into Free FattyAcids (free fatty acids). Free Fatty Acids will cause rancidity if too long in the store. this willdegrade the quality of the oil itself which can not be stored for too long. in addition to the watercontent of many, if the boiling of the palm fruit too quickly will cause the color of the oil red bycarotene dye (red). the sterilizer data is devoted to three temperatures of 1200C, 1300C and 1400C,at which temperature will be compared to find a good temperature on the sterilizer. The steam flowrate comes in the range of 25-30 ton/hour which will cook fresh fruit bunches with Single Peak,Double Peak, Triple Peak steaming, very high steam temperatures that will affect the efficiency ofthe sterilizer. Apart from high steam temperatures other factors affecting the sterilizer are the inletvapor flow rate, the temperature of the outflow vapor rate and the condensate water flow rate, theflow rate at the condensate water is influenced by the pressure inside the sterilizer. the efficiencywill be great if the vapor flow rate is less than the condensate flow rate, the efficiency of thesterilizer based on 80%-90% factory specification, after analyzing according to the data obtainedin the field efficiency of about 76.8%, with the efficiency that has been in get as well as temperature1200C, 1300C and 1400C then the quality of palm oil produced is clean enough to be stored anddurable.Keywords: Sterilizer, Temperature, Sterilizer Efficiency, Oil Quality